Machine learning-based multimedia services for business model evaluation. (January 2022) - Zhong, Xiaoying; Tian, Xuejiao; Thilak, K. Deepa; M, Anbarasan
Abstract: A business model evaluation refers to how a company uses its capital to provide value to consumers while optimizing income and growth. Entrepreneurs are facing important challenges in executing their market development based on resource-centered business models. Hence, the Multimedia-assisted Business Evaluation Model (MBEM) based on machine learning has been proposed to improve business efficiency. Multimedia has the right to prohibit third persons from infringing a commercial model that involves the selling and distributing sound files for digital content by sending patents for the online distribution of music and video. It can be useful to produce a broad range of design proposals and find the newest innovations to create modern solutions to challenging structures and become more competitive markets. A Decision Support System (DSSs) based on machine learning for information systems supports organizational and business decision-making. The experimental results show that the proposed MBEM model enhances business evaluation, decision making, performance, and profitability compared to other popular methods.